Analisis Digital Communication Dalam Meningkatkan Pengunjung Objek Wisata Pantai Dulanga Kabupaten Gorontalo - Akasse, Cahyadi Saputra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to analyze digital communication in increasing the number of visitors to the Dulanga beach tourism object, Gorontalo Regency. The research method used in this research is descriptive qualitative with a case study research approach. The data obtained comes from in-depth interviews (depth interview), participant observation, and documentation. Determination of informants is done by technique-purposive sampling based on people directly involved in the tourism promotion process at Dulanga beach. The results of the study show that the promotion process carried out on social media by the Gorontalo Regency government has had a positive impact on the development of tourism potential in Gorontalo Regency and especially on Dulanga beach itself. The social media used by the Gorontalo district government is Facebook, Instagram, Youtube, as well as website which is managed directly by the Gorontalo district government. With this social media, it can make it easier for the government to promote tourism potential and the public can access information about tourist objects that will be visited easily through social media itself.